Influence of Tsunami Aspect Ratio on Near and Far-Field Tsunami Amplitude - Natalia K. Sannikova; Harvey Segur; Diego Arcas (Geosciences, 2021)
This study presents a numerical investigation of the source aspect ratio (AR) influence on tsunami decay characteristics with an emphasis in near and far-field differences for two initial wave shapes Pure Positive Wave and N-wave. It is shown that, when initial total energy for both tsunami types is kept the same, short-rupture tsunami with more concentrated energy are likely to be more destructive in the near-field, whereas long rupture tsunami are more dangerous in the far-field. The more elongated the source is, the stronger the directivity and the slower the amplitude decays in the intermediate- and far-fields. We present evidence of this behavior by comparing amplitude decay rates from idealized sources and showing their correlation with that observed in recent historical events of similar AR.